ENERGY APPROACH IN THE STUDY OF GEOSYSTEMS AND TECHNOLOGIES OF REFORESTATION IN TRANSNISTRIA - B. I. Kochurov; N. A. Marunych (Юг России: экология, развитие, 2016)
The aim is to determine the optimal technology management that meets the challenges of energy-efficient nature management in forest ecosystems of Transnistria by means of the energy approach. As well as to introduce ecological and economic “energy rouble” based assessment of the effectiveness of the restoration of forest geosystems in Transnistria.Methods. For the energy assessment of forest geosystems we have used techniques by Russian scientists (A.S. Mindrin and A.V. Pozdnyakov, K.A. Shurkina, M.M. Ivanova, T.Sh. Fusella), modified and adapted to the specific regional conditions of Transnistria.Results. By using the energy approach and the ecological and economic “energy rouble” based assessment in Transnistria it has been found that reforestation technology number 3 is the least energy-intensive and, as a consequence, the most energy-efficient of all applied in Transnistria. In addition, taking into account the specificity of the technology, it helps the forest environment remain in almost unchanged condition, thus preserving biodiversity, forest communities. This technology reflects the economic and environmental interests, that is, it can be defined as technology of environmental management.Conclusions. The studies have allowed to significantly increase the energy intensity of human activity on the example of one of the forest enterprises of Transnistria. The proposed recovery technology with the use of the forest environment of parent plants and the elements of the natural regeneration (technology number 3) restores forest ecosystems naturally, preserving biodiversity and habitat forest communities. Thus, it is the direction of the effective environmental management capable to provide the basis for the recovery model of forest geosystems in the republic as well as neighboring countries and regions (including Russia).